The Reduction of Oxidative Stress in Dyslipidemic Sprague Dawley Rats with Exposure to Mulberry Leaf Extract and Simvastatin - Yugi Hari Chandra Purnama; Fifin Luthfia Rahmi; Banundari Rachmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Dyslipidemia induces oxidative stress, leading to the subendothelial accumulation of atherogenic lipoproteins and the initiation of reactive oxygen species (ROS) formation. Secondary metabolites such as flavonoids found in mulberry leaves can act as antioxidants, suppressing the production of free radicals responsible for oxidative stress. This study aims to evaluate the impact of mulberry leaf extract and simvastatins on MDA levels in dyslipidemic Sprague Dawley rats. This research is a true experimental type with a pre-post test with control group design. The samples in this study were mulberry leaves and Sprague Dawley rats. Mulberry leaves were extracted using the maceration method with 70% ethanol solvent, then continued with antioxidant testing using DPPH. The number of samples in this study was 30 male rats which were divided into 5 groups; group P1 (HFD + mulberry leaf extract), P2 (HFD + simvastatin), P3 (HFD + mulberry leaf extract + simvastatin) as well as the normal group and the negative control group. Mulberry leaf ethanol extract has an IC50 value of 5.61 ppm which is very strong category. The intervention was carried out for 8 weeks. MDA levels were checked before and after intervention. The results showed a significant decrease in MDA levels in treatment groups P1, P2 and P3. Changes in MDA levels between groups were tested using one way ANOVA with significant results p=0.000 (p < 0,05). Administration of mulberry leaf extract which is rich in flavonoids and simvastatin significantly reduces MDA levels in the blood of rats.